Magnetic Drug Navigation: Magnetically Navigated Protein Transduction In Vivo using Iron Oxide‐Nanogel Chaperone Hybrid (Adv. Healthcare Mater. 9/2021). Issue 9 (5th May 2021) - Kawasaki, Riku; Sasaki, Yoshihiro; Nishimura, Tomoki; Katagiri, Kiyofumi; Morita, Kei‐ichi; Sekine, Yurina; Sawada, Shin‐ichi; Mukai, Sada‐atsu; Akiyoshi, Kazunari
Abstract : In article number 2001988 by Yoshihiro Sasaki, Kazunari Akiyoshi, and co‐workers, the magnetic nanogel chaperone, comprising of self‐assembled polysaccharide nanogels and iron oxide nanoparticles, is developed for magnetically navigated in vivo protein transduction. Magnetic navigation enhances accumulation of the magnetic nanogel chaperone toward tumor tissues. Saporin‐loaded magnetic nanogel chaperone exhibits excellent anti‐tumor efficacy against oral cancer xenograft mice in vivo.